A kind of anti-aging PVC material

By adding organic modified natural rubber and functionalized silica in the preparation process of PVC material, the problem of aging of PVC material is solved, and its anti-aging, high temperature and wear resistance are significantly improved.

CN118772552BActive Publication Date: 2025-02-11XIONGXIAN JINGHUA PLASTIC PROD CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411013110.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-07-26
Publication Date
2025-02-11
Estimated Expiration
2044-07-26

AI Technical Summary

Technical Problem

PVC materials are susceptible to ultraviolet rays, heat, oxygen and humidity during long-term use, resulting in problems such as aging, brittleness, cracking and yellowing.

Method used

The material's wear resistance, aging resistance and flame retardant properties are enhanced by adding organic modified natural rubber and functionalized silica during the preparation of polyvinyl chloride material.

Benefits of technology

It effectively improves the anti-aging performance of polyvinyl chloride materials, enhances its high temperature and wear resistance, and makes the material more stable in long-term use.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118772552B_ABST
    Figure CN118772552B_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of composite materials, and discloses an anti-aging PVC material. The anti-aging PVC material comprises polyvinyl chloride, a plasticizer, low-density polyethylene, organically modified natural rubber, functionalized silica, a lubricant and a heat stabilizer, wherein the organically modified natural rubber is prepared by introducing a rigid structure into the structure of epoxidized natural rubber, and the functionalized silica is prepared by grafting a hindered phenol structure onto the surface of nano-silicon dioxide. Adding the prepared organically modified natural rubber and the functionalized silica into the preparation process of the PVC material can effectively improve the wear resistance, anti-aging and high temperature resistance of the PVC material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of composite materials, and in particular to an anti-aging PVC material. Background Art

[0002] Polyvinyl chloride (PVC) is a low-cost material that is resistant to acid and alkali corrosion, has good plasticity and good insulation properties. It is widely used in the footwear industry, pipes, daily necessities, wires and cables, and packaging films. Because of its excellent flexibility, wear resistance and waterproof properties. However, PVC materials will be affected by ultraviolet rays, heat, oxygen and humidity during long-term use, and these factors will accelerate its aging process. After aging, PVC materials may become brittle, cracked, and yellowed. In order to solve these problems, a variety of anti-aging technologies have been introduced in the research and development of PVC materials to maintain the stability of PVC material performance, and they need to be improved. Summary of the invention

[0003] The purpose of the present invention is to provide an anti-aging PVC material, which is prepared by preparing organic modified natural rubber and functionalized silica, and adding them into the preparation process of polyvinyl chloride material to effectively enhance the wear resistance, anti-aging and flame retardant properties of polyvinyl chloride material.

[0004] The purpose of the present invention can be achieved by the following technical solutions:

[0005] An anti-aging PVC material comprises the following raw materials in parts by weight: 70-80 parts of polyvinyl chloride, 20-35 parts of plasticizer, 10-20 parts of low-density polyethylene, 8-12 parts of organic modified natural rubber, 8-10 parts of functionalized silicon dioxide, 2-4 parts of lubricant, and 2-3 parts of heat stabilizer.

[0006] Further preferably, the plasticizer is any one of trioctyl trimellitate, trinonyl trimellitate or triisodecyl trimellitate; the lubricant is any one of polyethylene wax or paraffin wax; and the heat stabilizer is any one of zinc stearate or calcium stearate.

[0007] Further preferably, the method for preparing the organically modified natural rubber comprises the following steps:

[0008] Add epoxidized natural rubber and xylene to a flask equipped with a thermometer, mix well, then add 6-quinolineacetic acid and catalyst A, raise the system temperature to 100-110°C, keep the temperature for 3-4 hours, and after the reaction is completed, remove the solvent by reduced pressure distillation to obtain organic modified natural rubber.

[0009] More preferably, the epoxidation rate of the epoxidized natural rubber is 25%.

[0010] More preferably, the catalyst A is any one of tetrabutylammonium bromide or triethylbenzylammonium chloride.

[0011] By utilizing the effects of high temperature and catalyst, the epoxy groups in the epoxidized natural rubber structure can undergo a ring-opening reaction with the carboxyl groups in the 6-quinolineacetic acid structure, introducing a rigid structure into the structure of the epoxidized natural rubber and generating hydroxyl groups to obtain an organically modified natural rubber.

[0012] Further preferably, the method for preparing the functionalized silica comprises the following steps:

[0013] S1: Add nano-silica and toluene into a flask, raise the system temperature to 55-60°C, then add chloroacetyl chloride and an acid binding agent, and keep the temperature to react for 5-6 hours. After the reaction, filter, wash, and dry to obtain modified nano-silica;

[0014] S2: Disperse the modified nano-silica in N,N-dimethylformamide, raise the temperature to 80-90°C, add 3,5-di-tert-butyl-4-hydroxycinnamic acid and catalyst B, react for 2-3 hours, filter, wash, and vacuum dry to obtain functionalized silica.

[0015] More preferably, in step S1, the acid binding agent is any one of N,N-diisopropylethylamine or triethylamine.

[0016] Further preferably, in step S2, the catalyst B is any one of ferric chloride or aluminum chloride.

[0017] The chlorine element is introduced into the surface of the nano-silica by utilizing the reaction between the hydroxyl groups on the surface of the nano-silica and the acyl chloride in chloroacetyl chloride to obtain modified nano-silica. Under the catalytic action of the catalyst, the halogen functional groups in its structure can react with the carboxyl groups in the structure of 3,5-di-tert-butyl-4-hydroxycinnamic acid, thereby grafting a hindered phenol structure on the surface of the nano-silica to obtain functionalized silica.

[0018] Further preferably, the method for preparing the anti-aging PVC material comprises the following steps:

[0019] The first step: pouring parts by weight of polyvinyl chloride, plasticizer, low-density polyethylene, organic modified natural rubber, functionalized silica, lubricant and heat stabilizer into a mixer and mixing, stirring at a speed of 1000-1200 r / min for 2-4 hours, discharging the material, and obtaining a mixed material;

[0020] Step 2: Put the mixed material into a twin-screw extruder for mixing, extrusion and granulation to obtain anti-aging PVC material.

[0021] Further preferably, in the second step, the temperature of zone 1 of the twin-screw extruder is 145-150°C, the temperature of zone 2 is 150-160°C, the temperature of zone 3 is 165-175°C, the temperature of zone 4 is 180-200°C, and the temperature of zone 5 is 165-180°C.

[0022] Beneficial effects of the present invention:

[0023] (1) The present invention provides an anti-aging PVC material. Functionalized silica is added during the preparation of the polyvinyl chloride material. The silica itself can improve the wear resistance of the polyvinyl chloride material. After the hindered phenol structure is grafted on the surface of the nano-silicon dioxide, the agglomeration problem of silica can be effectively improved, and the compatibility between silica and polyvinyl chloride and other additives can be improved. In addition, the hindered phenol can react with oxygen-containing free radicals to generate stable aromatic oxygen free radicals, thereby terminating the transmission and growth of the free radical chain, thereby enhancing the anti-aging performance of the polyvinyl chloride material.

[0024] (2) The natural rubber used in the present invention can toughen polyvinyl chloride, so that the prepared polyvinyl chloride material has higher impact strength. After the natural rubber is organically modified, that is, a rigid structure is introduced, it is added to the preparation process of the polyvinyl chloride material to enhance the high temperature resistance of the polyvinyl chloride material. Under high temperature conditions, the hydroxyl groups generated in the organically modified natural rubber structure can interact with the chlorine atoms in the polyvinyl chloride structure, significantly improving the bonding strength between the two, further enhancing the high temperature resistance of the polyvinyl chloride material, and making the polyvinyl chloride material more stable under high temperature conditions, thereby improving its anti-aging performance.

[0025] Of course, any product implementing the present invention does not necessarily need to achieve all of the advantages described above at the same time. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the accompanying drawings required for describing the embodiments will be briefly introduced below. Obviously, the accompanying drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other accompanying drawings can be obtained based on these accompanying drawings without paying creative work.

[0027] Figure 1 This is the infrared spectrum of functionalized silica. DETAILED DESCRIPTION

[0028] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0029] Example 1

[0030] 1. Preparation of organically modified natural rubber

[0031] 5 g of epoxidized natural rubber and 60 mL of xylene were added to a flask equipped with a thermometer and mixed evenly. 2.8 g of 6-quinolineacetic acid and 0.5 g of tetrabutylammonium bromide were then added. The system temperature was raised to 100°C and the reaction was kept warm for 4 hours. After the reaction was completed, the solvent was removed by distillation under reduced pressure to obtain an organically modified natural rubber, wherein the epoxidation rate of the epoxidized natural rubber was 25%, which was purchased from the Chinese Academy of Tropical Agricultural Sciences.

[0032] The nitrogen content in the organically modified natural rubber was tested using the Vario EL Cube elemental analyzer from Elementar. After testing and analysis, the nitrogen content in the organically modified natural rubber was 1.32%, indicating that 6-quinolineacetic acid and epoxidized natural rubber reacted.

[0033] 2. Preparation of functionalized silica

[0034] S1: Add 6 g of nano-silica and 65 mL of toluene into a flask, raise the system temperature to 60°C, add 5.4 g of chloroacetyl chloride and 2.1 g of N,N-diisopropylethylamine, and keep the temperature to react for 5 h. After the reaction, filter, wash, and dry to obtain modified nano-silica;

[0035] S2: Disperse 3.5 g of modified nano-silica in 50 mL of N,N-dimethylformamide, raise the temperature to 90°C, add 2.8 g of 3,5-di-tert-butyl-4-hydroxycinnamic acid and 0.4 g of ferric chloride, react for 3 h, filter, wash, and vacuum dry to obtain functionalized silica.

[0036] The functionalized silica was prepared by potassium bromide tableting method. The prepared sample was placed on a Nicolet 5700 infrared spectrometer at a wavelength of 4000-500 cm -1 Test within the range, such as Figure 1 As shown, the functionalized silica has a peak at 3045 cm -1 The absorption peak of CH in the double bond appears at 3032cm -1 The absorption peak of CH in the benzene ring appears at 2941cm-1 The absorption peak of CH in methyl appears at 1768cm -1 The absorption peak of C=O appears at

[0037] 3. Preparation of anti-aging PVC materials

[0038] The first step: pour 70 parts by weight of polyvinyl chloride, 20 parts of triisodecyl trimellitate, 10 parts of low-density polyethylene, 8 parts of organically modified natural rubber, 8 parts of functionalized silica, 2 parts of polyethylene wax and 2 parts of calcium stearate into a blender, stir at a speed of 1000 r / min for 2 hours, and discharge to obtain a mixed material;

[0039] The second step: putting the mixed material into a twin-screw extruder for mixing, extrusion and granulation to obtain anti-aging PVC material, wherein the temperature of the first zone of the twin-screw extruder is 145°C, the temperature of the second zone is 150°C, the temperature of the third zone is 165°C, the temperature of the fourth zone is 180°C, and the temperature of the fifth zone is 165°C.

[0040] The organically modified natural rubber and functionalized silica prepared in this example were used in the following examples and comparative examples.

[0041] Example 2

[0042] Preparation of anti-aging PVC materials

[0043] The first step: pour 75 parts by weight of polyvinyl chloride, 25 parts of triisodecyl trimellitate, 15 parts of low-density polyethylene, 10 parts of organically modified natural rubber, 9 parts of functionalized silica, 3 parts of polyethylene wax and 2 parts of calcium stearate into a blender, stir at a speed of 1100 r / min for 3 hours, and discharge to obtain a mixed material;

[0044] The second step: putting the mixed material into a twin-screw extruder for mixing, extrusion and granulation to obtain anti-aging PVC material, wherein the temperature of the first zone of the twin-screw extruder is 148°C, the temperature of the second zone is 152°C, the temperature of the third zone is 170°C, the temperature of the fourth zone is 190°C, and the temperature of the fifth zone is 170°C.

[0045] Example 3

[0046] Preparation of anti-aging PVC materials

[0047] The first step: pour 75 parts by weight of polyvinyl chloride, 30 parts of triisodecyl trimellitate, 18 parts of low-density polyethylene, 11 parts of organically modified natural rubber, 9 parts of functionalized silica, 3 parts of polyethylene wax and 3 parts of calcium stearate into a blender, mix, stir at a speed of 1100 r / min for 3 hours, discharge, and obtain a mixed material;

[0048] The second step: putting the mixed material into a twin-screw extruder for mixing, extrusion and granulation to obtain anti-aging PVC material, wherein the temperature of the first zone of the twin-screw extruder is 150°C, the temperature of the second zone is 155°C, the temperature of the third zone is 172°C, the temperature of the fourth zone is 195°C, and the temperature of the fifth zone is 170°C.

[0049] Example 4

[0050] Preparation of anti-aging PVC materials

[0051] The first step: pour 80 parts by weight of polyvinyl chloride, 35 parts of triisodecyl trimellitate, 20 parts of low-density polyethylene, 12 parts of organically modified natural rubber, 10 parts of functionalized silica, 4 parts of polyethylene wax and 3 parts of calcium stearate into a blender, stir at a speed of 1200 r / min for 4 hours, and discharge to obtain a mixed material;

[0052] The second step: putting the mixed material into a twin-screw extruder for mixing, extrusion and granulation to obtain anti-aging PVC material, wherein the temperature of the first zone of the twin-screw extruder is 150°C, the temperature of the second zone is 160°C, the temperature of the third zone is 175°C, the temperature of the fourth zone is 200°C, and the temperature of the fifth zone is 180°C.

[0053] Comparative Example 1

[0054] Preparation of PVC materials

[0055] The first step: pour 80 parts by weight of polyvinyl chloride, 35 parts of triisodecyl trimellitate, 20 parts of low-density polyethylene, 10 parts of functionalized silica, 4 parts of polyethylene wax and 3 parts of calcium stearate into a blender, stir at a speed of 1200 r / min for 4 hours, and discharge to obtain a mixed material;

[0056] The second step: putting the mixed material into a twin-screw extruder for mixing, extrusion and granulation to obtain anti-aging PVC material, wherein the temperature of the first zone of the twin-screw extruder is 150°C, the temperature of the second zone is 160°C, the temperature of the third zone is 175°C, the temperature of the fourth zone is 200°C, and the temperature of the fifth zone is 180°C.

[0057] Comparative Example 2

[0058] Preparation of PVC materials

[0059] The first step: pour 80 parts by weight of polyvinyl chloride, 35 parts of triisodecyl trimellitate, 20 parts of low-density polyethylene, 12 parts of organic modified natural rubber, 4 parts of polyethylene wax and 3 parts of calcium stearate into a blender, stir at a speed of 1200 r / min for 4 hours, and discharge to obtain a mixed material;

[0060] The second step: putting the mixed material into a twin-screw extruder for mixing, extrusion and granulation to obtain anti-aging PVC material, wherein the temperature of the first zone of the twin-screw extruder is 150°C, the temperature of the second zone is 160°C, the temperature of the third zone is 175°C, the temperature of the fourth zone is 200°C, and the temperature of the fifth zone is 180°C.

[0061] Comparative Example 3

[0062] Preparation of PVC materials

[0063] The first step: pour 80 parts by weight of polyvinyl chloride, 35 parts of triisodecyl trimellitate, 20 parts of low-density polyethylene, 12 parts of epoxidized natural rubber, 10 parts of functionalized silica, 4 parts of polyethylene wax and 3 parts of calcium stearate into a blender, stir at a speed of 1200 r / min for 4 hours, and discharge to obtain a mixed material;

[0064] The second step: putting the mixed material into a twin-screw extruder for mixing, extrusion and granulation to obtain anti-aging PVC material, wherein the temperature of the first zone of the twin-screw extruder is 150°C, the temperature of the second zone is 160°C, the temperature of the third zone is 175°C, the temperature of the fourth zone is 200°C, and the temperature of the fifth zone is 180°C.

[0065] Comparative Example 4

[0066] Preparation of PVC materials

[0067] The first step: pour 80 parts by weight of polyvinyl chloride, 35 parts of triisodecyl trimellitate, 20 parts of low-density polyethylene, 12 parts of organically modified natural rubber, 10 parts of silicon dioxide, 4 parts of polyethylene wax and 3 parts of calcium stearate into a blender, stir at a speed of 1200 r / min for 4 hours, and discharge to obtain a mixed material;

[0068] The second step: putting the mixed material into a twin-screw extruder for mixing, extrusion and granulation to obtain anti-aging PVC material, wherein the temperature of the first zone of the twin-screw extruder is 150°C, the temperature of the second zone is 160°C, the temperature of the third zone is 175°C, the temperature of the fourth zone is 200°C, and the temperature of the fifth zone is 180°C.

[0069] Comparative Example 5

[0070] Preparation of PVC materials

[0071] The first step: pour 80 parts by weight of polyvinyl chloride, 35 parts of triisodecyl trimellitate, 20 parts of low-density polyethylene, 12 parts of epoxidized natural rubber, 10 parts of silicon dioxide, 4 parts of polyethylene wax and 3 parts of calcium stearate into a blender, stir at a speed of 1200 r / min for 4 hours, and discharge to obtain a mixed material;

[0072] The second step: putting the mixed material into a twin-screw extruder for mixing, extrusion and granulation to obtain anti-aging PVC material, wherein the temperature of the first zone of the twin-screw extruder is 150°C, the temperature of the second zone is 160°C, the temperature of the third zone is 175°C, the temperature of the fourth zone is 200°C, and the temperature of the fifth zone is 180°C.

[0073] Performance Testing

[0074] I. The PVC materials prepared in Examples 1 to 4 and Comparative Examples 1 to 5 of the present invention were prepared into standard samples, and the notched impact strength of the samples was tested with reference to the national standard GB / T1843-2008. The test results are shown in the following table:

[0075]

[0076] As can be seen from the above table, the notched impact strength of the PVC materials prepared in Examples 1 to 4 of the present invention is relatively large, because the organic modified natural rubber is added in the preparation process of the PVC material, so the PVC material has good toughness. The notched impact strength of the PVC materials prepared in Comparative Examples 2 to 5 is slightly lower than that of the examples, because the natural rubber that can toughen the PVC material is also added, so the prepared PVC materials also have a certain toughness. The PVC material prepared in Comparative Example 1 does not add the organic modified natural rubber in the preparation process of the PVC material, so the notched impact strength is small and the toughness is poor.

[0077] II. With reference to the national standard GB / T528-2009, the tensile strength of the PVC materials prepared in Examples 1 to 4 and Comparative Examples 1 to 5 of the present invention at room temperature was tested, and then the tensile strength of the PVC materials after the test in a heat aging test chamber was tested, wherein the test temperature was 120°C and the test time was 48 hours. The tensile strength retention rate was calculated using the formula [tensile strength after aging / tensile strength before aging × 100%]. Generally, the mechanical properties of PVC materials will decrease after aging, and the anti-aging performance of PVC materials is represented by the change in tensile strength. The test results are shown in the following table:

[0078]

[0079]

[0080] As can be seen from the above table, the tensile strength retention rates of the PVC materials prepared in Examples 1 to 4 of the present invention are relatively high, indicating that the prepared PVC materials all have excellent anti-aging properties. The tensile strength retention rates of the PVC materials prepared in Comparative Examples 1 and 3 are also relatively high. Since functionalized silica is added during the preparation of the PVC materials and a hindered phenol structure is grafted on the surface thereof, the anti-aging properties of the PVC materials are also good. However, the PVC materials prepared in Comparative Examples 2, 4 and 5 do not have functionalized silica added, so the tensile strength retention rates are low and the anti-aging properties are poor.

[0081] III. Referring to the national standard GB / T3960-2016, the friction coefficients of the PVC materials prepared in Examples 1 to 4 and Comparative Examples 1 to 5 of the present invention were tested. Generally speaking, the smaller the friction coefficient, the better the wear resistance of the surface material. The test results are shown in the following table:

[0082]

[0083]

[0084] As can be seen from the above table, the friction coefficient of the PVC materials prepared in Examples 1 to 4 of the present invention is small, indicating that the prepared PVC materials have good wear resistance. The friction coefficient of the PVC materials prepared in Comparative Example 1 and Comparative Example 3 to Comparative Example 5 is also small. Since nano-silicon dioxide that can improve the wear resistance of PVC is added during the preparation of the PVC material, the wear resistance is relatively good. The PVC material prepared in Comparative Example 2 has a large friction coefficient and poor wear resistance because no functionalized silicon dioxide is added.

[0085] IV. The PVC materials prepared in Examples 1 to 4 and Comparative Examples 1 to 5 of the present invention were placed in a thermogravimetric analyzer. In a nitrogen atmosphere, the temperature was raised from 25°C to 400°C at a heating rate of 10°C / min. The 200°C stabilization time of the samples was recorded to evaluate their high temperature resistance. The test results are shown in the following table:

[0086]

[0087]

[0088] As can be seen from the above table, the 200°C stability time of the PVC materials prepared in Examples 1 to 4 of the present invention is relatively long, indicating that the prepared PVC materials all have good high temperature resistance, making the PVC materials more stable under high temperature conditions and having better anti-aging properties. The 200°C stability time of the PVC materials prepared in Comparative Examples 2 and 4 is also relatively long, because organic modified natural rubber is added in the preparation process of the PVC materials, so the high temperature resistance and anti-aging properties are also good. The 200°C stability time of the PVC materials prepared in Comparative Examples 1, 3 and 5 is relatively short, because no organic modified natural rubber containing a rigid structure is added, so that the prepared PVC materials have poor high temperature resistance, are unstable under high temperature conditions, and are more prone to decomposition, so their anti-aging properties are also poor.

[0089] V. The PVC materials prepared in Examples 1 to 4 of the present invention and Comparative Examples 1 to 5 were made into samples of 15 mm×8 mm×2 mm. The samples were placed at a temperature of 100° C. and a relative humidity of 80% for 72 hours. The yellowness index change △YI of the samples before and after aging was tested using a Huntlab UltraScan VIS colorimeter. The test results are shown in the following table:

[0090]

[0091]

[0092] It can be seen from the above table that the yellowness index change value of the PVC materials prepared in Examples 1 to 4 of the present invention is small, indicating that the prepared PVC materials have good anti-aging performance. The yellowness index change value of the PVC materials prepared in Comparative Examples 1 and 3 is also small. Since functionalized silica containing a hindered phenol structure is added during the preparation of the PVC materials, the anti-aging performance of the PVC materials is also good. However, the PVC materials prepared in Comparative Examples 2, 4 and 5 do not add functionalized silica, so the yellowness index change value is large and the anti-aging performance is poor.

[0093] In the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "example", "specific example", or "some examples" etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, without contradiction.

[0094] The above contents are merely examples and explanations of the concept of the present invention. The technicians in this technical field may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the concept of the invention or exceed the scope defined by the claims, they should all fall within the protection scope of the present invention.

Claims

1. An anti-aging PVC material, characterized in that: The invention comprises the following raw materials in parts by weight: 70-80 parts of polyvinyl chloride, 20-35 parts of plasticizer, 10-20 parts of low-density polyethylene, 8-12 parts of organically modified natural rubber, 8-10 parts of functionalized silicon dioxide, 2-4 parts of lubricant, and 2-3 parts of heat stabilizer; The preparation method of the organic modified natural rubber comprises the following steps: Add epoxidized natural rubber and xylene to a flask equipped with a thermometer, mix well, then add 6-quinolineacetic acid and catalyst A, raise the system temperature to 100-110°C, keep the temperature for 3-4 hours, and after the reaction is completed, remove the solvent by vacuum distillation to obtain an organic modified natural rubber; The epoxidation rate of the epoxidized natural rubber is 25%; The catalyst A is any one of tetrabutylammonium bromide or triethylbenzylammonium chloride; The preparation method of the functionalized silica comprises the following steps: S1: Add nano-silica and toluene into a flask, raise the system temperature to 55-60° C., then add chloroacetyl chloride and an acid binding agent, and keep the temperature for 5-6 hours. After the reaction, filter, wash, and dry to obtain modified nano-silica; in step S1, the acid binding agent is any one of N,N-diisopropylethylamine or triethylamine; S2: Disperse the modified nano-silica in N,N-dimethylformamide, raise the temperature to 80-90°C, add 3,5-di-tert-butyl-4-hydroxycinnamic acid and catalyst B, react for 2-3 hours, filter, wash, and vacuum dry to obtain functionalized silica; in step S2, the catalyst B is any one of ferric chloride or aluminum chloride.

2. The anti-aging PVC material according to claim 1, characterized in that: The plasticizer is any one of trioctyl trimellitate, trinonyl trimellitate or triisodecyl trimellitate; the lubricant is any one of polyethylene wax or paraffin wax; and the heat stabilizer is any one of zinc stearate or calcium stearate.

3. The anti-aging PVC material according to claim 1, characterized in that: Preparation method of the anti-aging PVC material The following steps are involved: The first step: pouring parts by weight of polyvinyl chloride, plasticizer, low-density polyethylene, organic modified natural rubber, functionalized silica, lubricant and heat stabilizer into a mixer and mixing, stirring at a speed of 1000-1200 r / min for 2-4 hours, discharging the material, and obtaining a mixed material; Step 2: Put the mixed material into a twin-screw extruder for mixing, extrusion and granulation to obtain anti-aging PVC material.

4. The anti-aging PVC material according to claim 3, characterized in that: In the second step, the temperature of the twin-screw extruder zone 1 is 145-150°C, the temperature of zone 2 is 150-160°C, the temperature of zone 3 is 165-175°C, the temperature of zone 4 is 180-200°C, and the temperature of zone 5 is 165-180°C.

Citation Information

Patent Citations

  • Functional nano-titanium dioxide grafted with antioxidant molecules on surface and preparation method of functional nano-titanium dioxide

    CN108084494A

  • Rubber compound for outer rubber layer of rubber tube and preparation method of rubber compound

    CN114230880A